Workplace bullying, sleep problems and leisure-time physical activity: a prospective cohort study - Åse Marie Hansen; Maria Gullander; Annie Hogh; Roger Persson; Henrik A Kolstad; Morten Vejs Willert; Jens Peter Bonde; Linda Kaerlev; Reiner Rugulies; Matias Brødsgaard Grynderup (Nordic Association of Occupational Safety and Health (NOROSH), 2016)
OBJECTIVES: Workplace bullying is a potent stressor that may increase sleep problems. Since physical fitness improves resilience to stress, it seems plausible that recreational physical activities may moderate the association between bullying and sleep. The study aimed to examine prospectively whether (i) bullying increases the risk of sleep problems, and (ii) the association between bullying and sleep problems is moderated by leisure-time physical activity (LTPA). METHODS: The study sample comprised a cohort of public and private sector employees, who were enrolled into the Work Bullying and Harassment (WBH) cohort (N=3278) or the Psychosocial Risk Factors for Stress and Mental Disease (PRISME) cohort (N=4455). We measured workplace bullying using one question that was preceded by a definition of bullying. We used the Karolinska sleep questionnaire to assess sleep problems. The number of hours per week spent on LTPA estimated the degree of physical activity. RESULTS: Workplace bullying at baseline (T1) was associated with awakening problems and lack of restful sleep at follow-up (T2) but not with overall sleep problems and disturbed sleep. T1-LTPA did not moderate the association between T1-workplace bullying and T2-sleep problems. CONCLUSION: We found support that workplace bullying is related to development of T2-sleep problems, but this association seems not to be modified by LTPA.